Organising pneumonia during breast cancer treatment with trastuzumab - Liu, Wing-Kin; Gillibrand, Rebecca; Moonsie, Ian; Anand, Girija; José, Ricardo J. (Annals of Research Hospitals, 2019)
A 57-year-old female with early human epidermal growth factor receptor 2 (HER2) positive breast cancer on adjuvant trastuzumab and anastrozole treatment presented with difficulty breathing and fever. Chest X-ray revealed left lower zone consolidation. She was treated with several courses of antibiotics, and despite improvement in her inflammatory markers, the clinical and radiological picture did not. Microbiological cultures from bronchoalveolar lavage fluid were negative. Organising pneumonia was suspected and computed tomography (CT) guided lung biopsy confirmed this. Trastuzumab was suspected as the likely culprit and stopped. High dose steroids commenced and the patient recovered, but later as per the patient’s choice trastuzumab treatment was re-started and she re-developed similar symptoms to her previous presentation with chest X-ray showing new right middle zone consolidation, in the absence of infection, and recurrence of organising pneumonia was diagnosed confirming trastuzumab as the cause. She improved clinically on a higher dose of steroids.